If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(c + -11) = 12 Reorder the terms: 3(-11 + c) = 12 (-11 * 3 + c * 3) = 12 (-33 + 3c) = 12 Solving -33 + 3c = 12 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '33' to each side of the equation. -33 + 33 + 3c = 12 + 33 Combine like terms: -33 + 33 = 0 0 + 3c = 12 + 33 3c = 12 + 33 Combine like terms: 12 + 33 = 45 3c = 45 Divide each side by '3'. c = 15 Simplifying c = 15
| -2y+0=6y | | (4x-10)(-2)= | | 140=3x+8x+8 | | 5a+7=3a+39 | | 6w-10+-18w= | | 2(30)+8= | | 4+8=36 | | 1-(1/2)(-x+5)=2+3(1-x) | | 15-4x=32 | | 7x-5(2x+2)=-19 | | -14p=156 | | 5+5y-5y=5 | | 17+x=3+17 | | -2(x-8)=6(x+4)-8 | | 5x+8-7x-12= | | y=2x^2+36x+168 | | 5y+6x-3y-5x+4x= | | 5y+6x-3y-5y+4x= | | 15m-9=21 | | -2(x-8)=(6x+4)-8 | | 3.45x+2.5y=52 | | 2r-5=1r | | -2x(x-8)=(6x+4)-8 | | -6r-10s+8r+4s-6= | | x^2+2x=89 | | 3x^4+9x^3-25x^2+15x-50=0 | | 2(5+-.5y)+y=10 | | 9y-2+9y=6 | | 18=-6-x | | Y=6x^7-2cosx | | =12v^4-8v^3 | | 7t-4.6=10.1 |